Financial Development and Inflation-Unemployment Trade-off: Empirical Evidence from Developing and Developed Countries - Mohammad Ali Aboutorabi; Mehdi Hajamini; Sahar Tohidi (پژوهش‌های برنامه و توسعه, 2020)
In the growing literature on “Maco-Financial Economics” it is important to consider financial development as a supply-side policy and investigate its effects on macroeconomic variables such as economic growth, inflation, and unemployment. According to the literature, the simultaneous effect of financial development on inflation and unemployment is missing. This paper calculates a multi-lateral financial development index by Principle Components Analysis (PCA) for 20 selected countries during 1979Q1-2016Q4. Then, the augmented Phillips curve is estimated using ARDL model for each countries. The results reveal that the inflation-unemployment trade-off is significantly reduced in some developed and developing countries by financial policies, while some other developing countries (as Iran) are still encountered with of inflation-unemployment duality.In the growing literature on “Maco-Financial Economics” it is important to consider financial development as a supply-side policy and investigate its effects on macroeconomic variables such as economic growth, inflation, and unemployment. According to the literature, the simultaneous effect of financial development on inflation and unemployment is missing. This paper calculates a multi-lateral financial development index by Principle Components Analysis (PCA) for 20 selected countries during 1979Q1-2016Q4. Then, the augmented Phillips curve is estimated using ARDL model for each countries. The results reveal that the inflation-unemployment trade-off is significantly reduced in some developed and developing countries by financial policies, while some other developing countries (as Iran) are still encountered with of inflation-unemployment duality.